ChatGPT Integration in EFL Advanced Grammar Instruction: A Pedagogical Framework - Yayu Sri Rahayu; Wintarsih; Imas Suryati (Jomantara Indonesian Journal of Art and Culture, 2026)
This study addresses the growing integration of artificial intelligence in English as a Foreign Language (EFL) education, particularly in advanced grammar instruction where learners often face difficulties in mastering complex structures. It aims to examine how ChatGPT can support grammar learning based on established second language acquisition (SLA) theories and learners’ perceptions. The study employs a qualitative descriptive design supported by a small-scale survey involving undergraduate students. Data were collected through questionnaires and a systematic literature review and analyzed thematically. The findings reveal that ChatGPT provides significant pedagogical affordances, including immediate corrective feedback, promotion of learner autonomy, and contextualized language use. Students also reported positive perceptions regarding its usefulness and ease of use. These findings align with key frameworks such as the Interaction Hypothesis, Sociocultural Theory, and Focus on Form. The study concludes that ChatGPT can effectively enhance grammar instruction when integrated within a structured pedagogical framework. This research contributes to the development of AI-assisted language learning models and offers practical implications for EFL practitioners and curriculum designers. Keywords: ChatGPT; EFL Instruction; Grammar Learning; Language Pedagogy; Second Language Acquisition